Promoting out-of-season crops - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1986)
A major operation to promote out-of-season crops was established in 1984 in Niger to help people overcome the worst of the drought It generated considerable popular support: many government agencies and departments, NGOs (non-governmental...